Estimation of Carbonate Elastic Properties Using Nanoindentation and Digital Images - De Paula, Osni; Pervukhina, M.; Gurevich, Boris; Lebedev, Maxim; Martyniuk, M.; Piane, C. (EAGE, 2010)
Petrophysical properties of carbonate reservoirs are less predictable than the properties of silisiclastic reservoirs. The main reason for that is chemical interaction of carbonate rocks with percolating fluids, ion exchange and recrystallization in geological time. Quantification of the elastic variability of carbonate grains on the microscale is the first step to constrain models and to obtain more realistic predictions of practically important rock properties of carbonate reservoirs. In this study we present elastic moduli of an oolite sample from the Pleistocene Dampier Formation of Southern Carnarvon Basin, Western Australia obtained by the nanoindentation technique.Young moduli of this highly heterogeneous sample are measured at 49 points regularly distributed in a 70x70micrometer rectangular grid on the surface. The frequency diagram shows bimodal distribution of the Young moduli that correspond to dense calcite phase and rare (dissolved) calcite phase. These two solid phases are apparent in the high resolution scanning electron microscope images. We used the obtained moduli of the dense and rare phases for numerical modelling of elastic properties of the carbonate sample from micro-CT images. The results of the numerical modelling using finite element code are compared with the elastic moduli obtained from acoustic velocities measured by ultrasonic technique.